Xuebijing Protects Against Septic Acute Liver Injury Based on Regulation of GSK-3β Pathway - Cao, Liping; Li, Zhenghong; Ren, Yi; Wang, Mengmeng; Yang, Zhizhou; Zhang, Wei; Han, Xiaoqin; Yao, Mengya; Sun, Zhaorui; Nie, Shinan (Frontiers in Pharmacology, 2021)
Xuebijing (XBJ), the only drug approved for the treatment sepsis and multiple organ dysfunction, and its protective effects against acute liver injury (ALI) and its mechanism. The aim of this study was to evaluate the protective effect of XBJ on cecal ligation and perforation (CLP)-induced mouse ALI model and LPS-induced RAW264.7 cell ALI model. Mice were pretreated with XBJ before the CLP model was established, and serum and liver tissues were collected at the end of the experiment to assess the levels of inflammatory factors and liver injury. Results showed that XBJ pretreatment reduced liver/body weight, aspartate aminotransferase (AST) and alanine aminotransferase (ALT) activities in serum, and inhibited levels of pro-inflammatory factors in serum. Cells were treatment with XBJ and modeled by LPS modeling increased cell viability in the XBJ-treated group compared to the model group and XBJ also decreased serum pro-inflammatory factors in a dose-dependent manner. Western blot detected that XBJ also up-regulated the phosphorylated levels of glycogen synthase kinase-3β (p-GSK-3β) and cAMP-response element-binding protein (p-CREB) and down-regulated the phosphorylated level of nuclear factor kappa-B (p-NF-κB) in liver and cell. After overexpression of GSK-3β in cells, the mechanism was further investigated using CO-IP analysis. The binding of p-NF-κB and p-CREB to CREB-binding protein (CBP) was increased and decreased, respectively, indicating that GSK-3β regulated inflammation by regulating the binding of p-NF-κB and p-CREB to CBP. The present studies suggested that the hepatoprotective effect of XBJ may be through up-regulation of GSK-3β (Ser9) and increasing the binding of p-CREB to CBP, thereby alleviating the inflammatory response.